(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY: The American Heart Association (AHA) developed a concept to measure cardiovascular health in populations. We aimed to analyse participants in the Swiss Longitudinal Cohort Study (SWICOS) according to the AHA concept. METHODS: We analysed cardiovascular health according to the AHA concept in all 474 participants of the prospective, population-based SWICOS study who were 18 years or older. The AHA concept uses seven health metrics of known cardiovascular risk factors (blood pressure, total cholesterol, blood glucose, smoking, body weight, physical activity and diet), and classifies each health metric according to three levels (ideal, intermediate and poor) using pre-defined cut-offs. RESULTS: Ideal cardiovascular health for three or more of the seven health metrics was found in 259 participants (54.9%; 95% confidence interval [CI] 50.1–59.4%), but a relevant number of participants (n = 213, 45.1%, 95% CI 40.6–49.7%) showed ideal cardiovascular health for only two or fewer of the seven health metrics. Poor cardiovascular health for three or more of the seven health metrics was found in 40 participants (8.5%; 95% CI 6.1–11.4%); a majority of 432 participants (91.5%; 95% CI 88.6–93.9%) showed a poor level for only two or fewer of the seven health metrics. CONCLUSIONS: Overall, we found favourable results for cardiovascular health in the population-based SWICOS cohort. Nevertheless, we see the need for further health prevention campaigns given the fact that a relevant proportion of the participants could optimise their cardiovascular health. Clinical Trial Registration Number: NCT02282748